Rethinking the Management of Optic Pathway Gliomas: A Single Center Experience - Del Baldo, Giada; Cacchione, Antonella; Dell’Anna, Vito Andrea; Merli, Pietro; Colafati, Giovanna Stefania; Marrazzo, Antonio; Rossi, Sabrina; Giovannoni, Isabella; Barresi, Sabina; Deodati, Annalisa; Valente, Paola; Ferretti, Elisabetta; et al. (Frontiers in Surgery, 2022)
Background: Optic pathway gliomas (OPGs) are rare neoplasms in children with an unpredictable clinical course. Approximately 15% of OPGs occur in patients affected by neurofibromatosis type 1 (NF1): the clinical course of these cases is more indolently than sporadic ones, and NF1 patients less frequently require treatment including surgery. Instead, over 90% of sporadic OPGs require one or more therapeutic approaches. The management of OPG is controversial. They are also characterized by a high risk of morbidity including hypothalamic damage, endocrine deficits, visual deficit and/or neurological impairment. Materials and methods: In this paper, we evaluated visual and endocrinological outcomes of a population of OPG followed at our center from 2013 to 2021, with a particular emphasis on the role of surgery. Results: Twenty-six patients were included in this study (mean age of 40.7 months). Tumor location on imaging was described by the Dodge classification. Five cases had NF 1. Thirteen cases received biopsy and 13 were partially resected. Histopathology revealed 19 cases of pilocytic astrocytomas, 2 pilomyxoid astrocytoma and 5 ganglioglioma. All the patients required a post-surgical adjuvant treatment according to current indications for low-grade gliomas. Molecular studies (BRAF status and mTOR/pmTOR pathway) have been performed in 24/26 patients, following for the use of target therapy in 11 of these patients. In our study we found that patients underwent biopsy have a better visual and endocrinological outcomes rather than patients with a tumor debulking. The five-year overall survival rate is 98% with a mean follow-up of 60 months. Conclusions: Many children with OPGs survive with a residual tumor. They suffer from chronic diseases such as endocrine dysfunction, visual disturbance, motor deficits and poor quality of life. All patients need comprehensive diagnostic work-up including neuroimaging, clinical evaluations and neuropathology approach; at the same time, they need therapeutic decisions and concepts for the choice of timing and type of neurosurgical intervention, chemotherapy and target therapy as well as surveillance and rehabilitation to maximize survival and overall functional outcomes. Our study showed that minimal invasive surgery with the purpose of molecular characterization of the tumor is desirable to reduce morbidity correlate to surgery.